Pobreza Rural - Fallas, Helio (2002)
The economic policy in Costa Rica during the l980s and 1990s is outlined here to shed light on its incidence in rural affairs. This is the basis for proposing a description of what the author understands today by rural affairs, in recognition of the fact that this setting has changed significantly in recent decades. This serves as a background to present rural poverty. Who are the poorest in Costa Rica? Which households are the poorest? And in what areas can they mainly be found? The article concludes by suggesting policies that would contribute substantially to the elimination of poverty.